Urban Heat Island Phenomenon in Tropical Countries: Analysis of the Wake Flow Behind Slender High-Rise Building - Muhammad Arifuddin, Fitriady; Nurizzatul Atikha, Rahmat; Ahmad Faiz, Mohammad (Springer Link, 2023)
Urban Heat Island (hereafter, UHI) is a phenomenon described by an increased temperature in an urban area compared to the temperature of its surrounding